Upaya Guru Mengatasi Kesulitan Membaca Permulaan Pada Peserta Didik Kelas 1 MIM 6 Kota Padang - Abdul Basit; Martin Kustati; Nana Sepriyanti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2023)
This study aims to determine the factors that influence the difficulty of beginning reading in and how the teacher's efforts in overcoming the difficulty of beginning reading in students. This study used a descriptive qualitative approach, with 38 students in grade 1 MIN 6 Padang as the subject. Data collection techniques used observation, interviews and documentation. The results of the study show that the factors that influence the difficulty of reading at the beginning of grade 1 MIN 6 Padang City are: Lack of attention from parents, often forgetting letters, peer environment, lack of confidence, difficulty spelling. Furthermore, this study also shows that the teacher's efforts in overcoming reading difficulties at the beginning of class 1 MIN 6 Padang City, namely the dominant teacher uses the syllable method, the teacher increases attention and directs when learning takes place, provides motivation and advice, lends books in the library, and provides hours addition. So it can be concluded that the teacher's efforts in overcoming students' reading difficulties are very influential for students who have initial reading difficulties